Pengaruh Kedisiplinan Pegawai Negeri Sipil Terhadap Kinerja Pada Dinas Transmigrasi Dan Tenaga Kerja Provinsi Sulawesi Barat - Brilian, Muh. Hendrik G; Alqirana, Elsya (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
Work discipline refers to an individual’s ability to comply with organizational rules as a form of self-control in achieving organizational goals. However, phenomena of low work discipline are still found, as reflected in attendance levels, lateness, and non-compliance with official working hours, which hinder the achievement of organizational objectives. This study aims to identify the effect of work discipline on employee performance at the Office of the Transmigration and Manpower Agency of West Sulawesi Province. The theoretical framework is based on human resource management concepts, work discipline according to Hasibuan, which includes compliance, punctuality, responsibility, orderliness, and work motivation, as well as employee performance according to Kasmir, which is measured through quality, quantity, timeliness, and teamwork ability. This study aims to examine the effect of work discipline on the performance of Civil Servants at the Transmigration and Manpower Office of West Sulawesi Province. The research employed a quantitative approach, with data collected through questionnaires. The research sample consisted of 25 civil servants selected using purposive sampling from a total population of 94 civil servants. Data analysis was conducted using quantitative methods to test the relationship between work discipline and employee performance. The results show that work discipline has a significant effect on employee performance, with a significance value of < 0.05. It can be concluded that the higher the level of work discipline among civil servants, the better the performance achieved.